The cultural heritage tourism of Banten: Potentials, commercialization, and the challenges of sustainability - Enji Azizi; Mira Nurhikmat; Peni Astuti (Universitas Islam Sultan Agung, 2026)
Cultural heritage tourism plays a strategic role in strengthening local identity while enhancing destination attractiveness through authentic tourist experiences. This study aims to analyze the effects of commercialization, object-based authenticity, existential authenticity, and convenience on tourist satisfaction and loyalty in cultural heritage destinations across Banten Province. A quantitative research approach was employed using primary data collected from 1,540 tourist respondents through structured questionnaires. The questionnaire served as the research instrument, and the data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique with the SmartPLS application. The results show that commercialization positively affects object authenticity (O = 0.062; p = 0.007), although the effect size is small. Object authenticity has a strong effect on existential authenticity (O = 0.825; p = 0.000). Furthermore, existential authenticity significantly influences tourist satisfaction (O = 0.688; p = 0.000) and loyalty (O = 0.790; p = 0.000). In contrast, commercialization has a negative effect on satisfaction (O = -0.045; p = 0.023) and loyalty (O = -0.051; p = 0.004). Additionally, ease strengthens the relationship between commercialization and object authenticity (O = 0.092; p = 0.000). Overall, all hypotheses are supported (p < 0.05), indicating that the model is statistically robust in explaining tourist satisfaction and loyalty. The study provides both theoretical and practical contributions for destination managers in designing sustainable cultural heritage tourism strategies that are not solely profit-oriented but also focused on preserving cultural values and enhancing the overall quality of tourist experiences.